The effect of cognitive style on the analysis ability of grade 4 elementary school students - Susiloningsih, Wahyu; Susilo, Herawati; Zainuddin, Mohammad; Kuswandi, Dedi; Suciptaningsih, Oktaviani Adhi; Faizah, Hanim (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
The purpose of this study was to determine the relationship between cognitive style (reflective and impulsive) on students' analytical abilities. Analytical ability is part of learning outcomes. There are seven levels of cognitive learning outcomes which include knowledge, understanding, application, analysis, synthesis, evaluation, and creative problem-solving. Students' analytical abilities are influenced by many things, one of which is cognitive style. Cognitive style is a way of accepting and managing attitudes towards information, as well as habits related to the world of individual learning. Reflective and impulsive cognitive styles are cognitive styles with indicators of time understanding concepts. Reflective cognitive styles usually take a long time to respond, but consider all available options, and have high concentration while learning. Meanwhile, students with an impulsive cognitive style are the opposite. The approach used in this study is a correlational and multiple regression approach. The variables in this study are reflective cognitive style and impulsive cognitive style as independent variables and analytical skills as the dependent variable with a population of 130 students. The results showed that there was a relationship between students' cognitive style and analytical skills. The greater the cognitive style score, the greater the analytical ability score. Then the cognitive style affects the analytical ability of 19.9%, where the other 80.1% is influenced by other factors.